The Role of Adolescents in Stunting Prevention in Digital Era - Sumual, Herry; G.J. Soputan (JR Education, 2023)
The quality of human resources starts from the First 1000 Days of Life. Young women are the forerunner to give birth to the next generation. Attitudes and healthy lifestyle behaviors of a teenager can contribute to preventing stunting. The purpose of this activity is to educate young women on healthy living behaviors in an effort to prevent stunting. The method of implementing this activity used counseling/education for 64 participants. The results achieved by the youth were that 64 people had knowledge about stunting prevention. It is hoped that youth can become agents of change as a benefit of this community service activity.